Pengaruh Harga, Nilai Pelanggan dan Citra Perusahaan terhadap Kepuasan Pelanggan: (Studi pada Usaha Ayam Potong Peternakan La Lati di Desa Bente Kecamatan Kabawo Kabupaten Muna) - Yusuf; Muhammad Taufik; Hastuti Hastuti; Wa Ode Usna; Ariawan Ariawan (Journal of Technopreneurship on Economics and Business Review, 2022)
This study aims to examine and analyze the effect of price, customer value, and company image on customer satisfaction in La Lati's broiler business. This research was conducted on 50 customers of La Lati's beef cattle business. The study was conducted using a questionnaire instrument that has been tested for validity and reliability. The analytical tool used is multiple linear regression analysis. Based on the results of data analysis and hypothesis testing, it was found that simultaneously and partially price, customer value and company image had a positive and significant effect on customer satisfaction.